Desentraliasi Diri dalam Mengurangi Tingkat Kecemasan Berkomunikasi ketika Presentasi Mahasiswa IAIN Parepare - Irmawati, Yesi (Indonesian Journal of Islamic Counseling, 2022)
This research examines self-desensitization techniques in reducing communication anxiety levels during student presentations. This research was carried out because of the anxiety problems experienced by fellow students, so it must be handled quickly so that students do not feel disturbed by the situation they are feeling. The aim to be achieved in this research is to find out the situation before and after it is given. As well as being able to find out whether self-desensitization techniques can reduce the level of communication anxiety during presentations by BKI IAIN Parepare students. This type of research is quantitative pre-experimental using a one group pretest-posttest design. The results of research and pre-experimental actions obtained in research using a sample of 11 BKI IAIN Parepare students experienced a decrease in student anxiety as seen from the mean before being given treatment of 27.54 and the mean after being given treatment of 16.90. This is also proven by the condition tcount > ttable (9.76 > 1.812). Thus, the level of communication anxiety during presentations by BKI IAIN Parepare students decreased after being given self-desensitization techniques. So it can be concluded that self-desensitization techniques can reduce the level of communication anxiety of BKI IAIN Parepare students. It can be concluded that the hypothesis Ho is rejected and Ha is accepted.